Environmental footprint of voltammetric sensors based on screen-printed electrodes: an assessment towards "green" sensor manufacturing - Ahamed, Ashiq (2022)
Voltammetric sensors based on screen-printed electrodes (SPEs) await diverse applications in environmental monitoring, food, agricultural and biomedical analysis. However, due to the single-use and disposable characteristics of SPEs and the scale of measurements performed, their environmental impacts should be considered. A life cycle assessment was conducted to evaluate the environmental footprint of SPEs manufactured using various substrate materials (SMs: cotton textile, HDPE plastic, Kraft paper, graphic paper, glass, and ceramic) and electrode materials (EMs: platinum, gold, silver, copper, carbon black, and carbon nanotubes (CNTs)). The greatest environmental impact was observed when cotton textile was used as SM. HDPE plastic demonstrated the least impact (13 out of 19 categories), followed by ceramic, glass and paper. However, considering the end-of-life scenarios and release of microplastics into the environment, ceramic, glass or paper could be the most suitable options for SMs. Amongst the EMs, the replacement of metals, especially noble metals, by carbon-based EMs greatly reduces the environmental footprint of SPEs. Compared with other materials, carbon black was the least impactful on the environment. On the other hand, copper and waste-derived CNTs (WCNTs) showed low impacts except for terrestrial ecotoxicity and human toxicity (non-cancer) potentials. In comparison to commercial CNTs (CCNTs), WCNTs demonstrated lower environmental footprint and comparable voltammetric performance in heavy metal detections, justifying the substitution of CCNTs with WCNTs in commercial applications. In conclusion, a combination of carbon black or WCNTs EMs with ceramic, glass or paper SMs represents the most environmentally friendly SPE configurations for voltammetric sensor arrangement.